The influence of brand image and service features on e-wallet reuse intention (study of gopay e-wallet users) - Asy Syifa, Alifiya Adhiya; Malini, Helma; Purmono, Bintoro Bagus; Barkah, Barkah; Marumpe, Dody Pratama (Institute of Computer Science (IOCS), 2024)
Technological advances have significantly influenced individual behavioral tendencies in transactional activities, for example, e-wallet payments. E- wallet payments can potentially increase online consumer transactions' convenience, practicality, speed, and security. Gopay offers a comprehensive range of non-cash payment services through one platform in Indonesia, covering many transactions, including transportation, money transfers, online shopping, transactions at affiliated merchants, savings, and monthly bill payments. The objective of this study is to analyse the impact of brand image and service features on the reuse intention the Gopay e-wallet. Additionally, customer satisfaction will be investigated as a mediating in this relationship. The research sample consists of persons who possess the Gopay e-wallet application. A total of 233 participants were involved in the survey as the means of data collecting. The study utilised purposive sampling as the sampling method, employing the Structural Equation Modelling (SEM) and AMOS statistical methodologies. The result of the study indicate that Brand Image has a significant positive impact on Reuse Intention. Service features also exhibit a significant positive influence on reuse intention. Customer satisfaction demonstrates a significant positive impact on reuse intention. Brand Image additionally has a significant positive impact on customer satisfaction. Service features exert a positive and significant influence on customer satisfaction. Meanwhile, customer satisfaction mediates the relationship between Brand Image and reuse intention. Customer satisfaction also serves as a mediator between service features and reuse intention.